Factors influencing effectiveness of individual investor’s decision making: evidence from Sri Lankan stock market - Thanusan, S.; Kengatharan, L. (North South Business Review, Volume 10, Number 1, December 2019, 2019)
The investor decision making plays an important role in the investor’s return. However, the factors influencing investment decision making of individuals can differ from person to person because of their personal, psychological, economical, social and environmental factors. Therefore, the main objective of this study is to determine the factors influencing effectiveness of individual investor’s decision making in Sri Lankan stock market. 150 individual investors who are involving in stock market activities from Jaffna district have been selected for this survey. Self- administered and structured questionnaires were used to collect the relevant data from investors. The questionnaire constituted 34 items which are consisted in three parts like demographic information, factors influencing effectiveness of individual investor decision making and questions related with the effectiveness of investor’s decision making. Accounting information, neutral information, self - image/firm image, advocate recommendation and personal financial needs have been considered as explanatory variables and effectiveness of individual investor decision making has been considered as outcome variable. Descriptive, correlation and regression analysis have been used to analyse the data with aid of SPSS (version 20.0). Cronbach’s Alpha was used measure the reliability of the collected data. As per the results of the regression analysis, accounting information, neutral information and self-image/firm image have significant influence on effectiveness of individual investor’s decision making while advocate recommendation and personal financial needs have not significantly influenced on effectiveness of individual investor’s decision making in stock market. Outcome of the survey may be considered by current and future investors to make their effective investment decision.
Keywords: Accounting information; Neutral information; Self-image/firm image; Personal financial needs; Investor decision making; Advocate recommendation